ANALISIS KEMAMPUAN LITERASI EMOSI : ASPEK MENGELOLA EMOSI PADA SISWA KELAS V SD - Juita Maulida; Seni Apriliya, Asep Nuryadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the emotional literacy of fifth grade elementary school students, focusing on the dimension of managing emotions. The background of the research is based on the importance of good emotion management to support learners' academic and social development. This research uses a qualitative approach with the classroom ethnography method. Data were obtained through observation of 31 learners, as well as in-depth interviews with 4 learners and a teacher in one of the elementary schools in Tasikmalaya City. The results show that most learners still face difficulties in controlling emotions, especially in situations that cause emotional distress. Negative emotions such as anger and disappointment are often expressed through impulsive behavior, such as speaking harshly, hitting or staying away from social interactions. Despite teachers' efforts to provide support through personal and empathic approaches, these results confirm the need for systematic integration of emotional literacy in the learning process to help learners recognize, understand and manage emotions more effectively.